Association between Gender and Anxiety among Covid-19 Patients: A Meta-Analysis - Zuraida Zulkarnain; Arum Nuryati; Desif Upix; Adilla Misi; Andi Siswanto; Atik Handariati; Zadia Dara; Alfiana Nur Nur Rohmani; Saryanto Saryanto (Journal of Health Policy and Management, 2021)
Background: The COVID-19 outbreak rapidly spread worldwide, with a significant number of cases and deaths causing anxiety, especially among the sufferers. Biologically, males and females show different psychological responses to the events at hand. This study aimed to examine the association between gender and anxiety among COVID-19 patients.Subjects and Method: This study was a meta-analysis. The articles were obtained from databases PubMed and Scopus using keywords "Anxiety" OR "anxiety disorder" AND "COVID-19 Patients" OR "Patients with COVID-19" OR "Hospitalized" AND "Risk factors" OR "determinants" OR "Gender" OR "Factors associated". The articles included in this study were full-text with a cross-sectional design, discuss-ed the association between gender and anxiety among COVID-19 patients, published in English, studies located in Asia. The final results were presented in Adjust Odds Ratio (aOR) or Standardized Mean Difference (SMD). Data analysis was performed using Revman 5.3 software, with generic inverse variance data type for categorical outcome group (CtOG) articles and continuous data type for continue outcome group (CnOG).Results: 9 articles were analyzed, including 4 articles CtOG and 5 articles CnOG. The  forest plot of both categorical and continue outcomes showed consistent result that among COVID-19 patients  who hospitalized with mild to severe symptoms. Female patients significantly had higher anxiety event (aOR= 2.19; 95% CI= 1.60 to 2.99; p<0.001; I2= 0% and SMD= 0.35; 95% CI= 0.21 to 0.49; p<0.001; I2= 12%).Conclusion: Among COVID-19 patients, the female gender has a significantly higher risk of suffering from anxiety than the male gender.Keywords: anxiety, COVID-19Correspondence: Zuraida Zulkarnain. Research and Development Center of Traditional Medicinal and Medicinal Plants, Karanganyar, Central Java. Mobile: 081393933862. e-mail: zuraida.zu@gmail.com.Journal of Health Policy and Management (2021), 06(02): 94-106https://doi.org/10.26911/thejhpm.2021.06.02.02